Analisis Pembentukan Perjanjian Internasional untuk Menangani Krisis Penipisan Ozon akibat Emisi Orbital Spacecraft (RechtJiva, 2024)
This research aims to establish the regulatory framework for emissions generated by orbital spacecraft within the scope of international law, particularly space law and international environmental law, and to formulate a new international agreement that can address the emissions issues arising from orbital spacecraft. In analyzing these issues, the author employs a normative legal method, utilizing legislative and conceptual approaches. The Outer Space Treaty, as the primary agreement regulating all activities in outer space, proves inadequate in addressing the existing problems. Article IX, considered the closest provision to addressing the issue of orbital spacecraft emissions, still falls short and fails to provide a comprehensive solution. The Montreal Protocol, as the principal agreement related to compounds potentially causing ozone depletion, also falls short in evaluating the threat posed by orbital spacecraft emissions due to the limited coverage of regulatory jurisdiction. The regulatory vacuum concerning the impact of orbital spacecraft emissions on ozone depletion needs to be promptly addressed through the creation of a new international agreement. The formation of such an agreement should adhere to existing systematic structures, and the substance of the new agreement must be able to accommodate on-the-ground issues while maintaining an environmental perspective.